The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3846/bme.2020.12712
|View full text |Cite
|
Sign up to set email alerts
|

Solutions for Improving the Partnership Between Airport and Airline Companies

Abstract: Purpose – For every country’s economy, air transport is strategically and vitally important. For improving the quality of air transport services provision, partnerships between airports and airlines need to be encouraged more. The application of partnerships leads to quality improvements of services provided by companies and raises the efficiency of used practices. A number of the factors, which determine the effective partnership between organisations operating in the aviation sector, is examined on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…In the study, which was carried out by considering many airlines and airports with game theory, it was concluded that the airport preferred to share its revenue with the dominant airline to obtain the optimum benefit. Tunčikienė and Katinas (2020) emphasized that partnerships between airports and airlines should be further encouraged to improve the quality of air transport services. They established criteria for determining the factors of an effective partnership between airports and airlines and evaluating the positive effects of airport cooperation activities.…”
Section: Conceptual Framework and Literature Researchmentioning
confidence: 99%
“…In the study, which was carried out by considering many airlines and airports with game theory, it was concluded that the airport preferred to share its revenue with the dominant airline to obtain the optimum benefit. Tunčikienė and Katinas (2020) emphasized that partnerships between airports and airlines should be further encouraged to improve the quality of air transport services. They established criteria for determining the factors of an effective partnership between airports and airlines and evaluating the positive effects of airport cooperation activities.…”
Section: Conceptual Framework and Literature Researchmentioning
confidence: 99%